Analytical solution of diffusion model for nutrient release from controlled release fertilizer - Irfan, S.A. (Institute of Physics Publishing, 2017)
An analytical method has been developed to solve the initial value problem which arises from Fick's diffusion equation encountered in the modelling of the Controlled Release Fertilizers. The proposed analytical solution is developed using the modified Adomian decomposition method. This method does not require the discretization method, reliability and efficiency of this method is more and it also reduces the calculation time. The model has predicted the effect of granule radius and diffusion coefficient on the nutrient release and total release time of Controlled Release Fertilizer. Model has predicted that increase in the radius of granule reduces the release and vice versa in case of diffusion coefficient. Detailed understanding of these parameters helps in improved designing of Controlled Release Fertilizer. © Published under licence by IOP Publishing Ltd.